Every gene everywhere all at once: High-precision measurement of 3D chromosome architecture with single-cell Hi-C - Chi, Yi; Shi, Jenny; Xing, Dong; Tan, Longzhi (Frontiers in Molecular Biosciences, 2022)
The three-dimensional (3D) structure of chromosomes influences essential biological processes such as gene expression, genome replication, and DNA damage repair, and has been implicated in many developmental and degenerative diseases. In the past 2 centuries, 2 complementary genres of technology—microscopy, such as fluorescence in situ hybridization (FISH), and biochemistry, such as chromosome conformation capture (3C, or Hi-C)—have revealed general principles of chromosome folding in the cell nucleus. However, the extraordinary complexity and cell-to-cell variability of chromosome structure necessitate new tools with genome-wide coverage and single-cell precision. In the past decade, single-cell Hi-C emerges as a new approach that builds upon yet conceptually differs from bulk Hi-C assays. Instead of measuring population-averaged, statistical properties of chromosome folding, single-cell Hi-C works as a proximity¬-based “biochemical microscope” that measures actual 3D structures of individual genomes, revealing features hidden in bulk Hi-C such as radial organization, multi-way interactions, and chromosome intermingling. Single-cell Hi-C has been used to study highly dynamic processes such as the cell cycle, cell type–specific chromosome architecture (“structure types”), and structure–expression interplay, deepening our understanding of DNA organization and function.